Florally rich habitats reduce insect pollination and the reproductive success of isolated plants. Issue 16 (11th July 2017) - Evans, Tracie M.; Cavers, Stephen; Ennos, Richard; Vanbergen, Adam J.; Heard, Matthew S.
Abstract: Landscape heterogeneity in floral communities has the potential to modify pollinator behavior. Pollinator foraging varies with the diversity, abundance, and spatial configuration of floral resources. However, the implications of this variation for pollen transfer and ultimately the reproductive success of insect pollinated plants remains unclear, especially for species which are rare or isolated in the landscape. We used a landscape‐scale experiment, coupled with microsatellite genotyping, to explore how the floral richness of habitats affected pollinator behavior and pollination effectiveness. Small arrays of the partially self‐compatible plant Californian poppy ( Eschscholzia californica) were introduced across a landscape gradient to simulate rare, spatially isolated populations. The effects on pollinator activity, outcrossing, and plant reproduction were measured. In florally rich habitats, we found reduced pollen movement between plants, leading to fewer long‐distance pollination events, lower plant outcrossing, and a higher incidence of pollen limitation. This pattern indicates a potential reduction in per capita pollinator visitation, as suggested by the lower activity densities and richness of pollinators observed within florally rich habitats. In addition, seed production reduced by a factor of 1.8 in plants within florally rich habitats and progeny germination reduced by a factor of 1.2. We show this to be a consequence of self‐fertilization within the partially self‐compatible plant, E. californica . These findings indicate that locally rare plants are at a competitive disadvantage within florally rich habitats because neighboring plant species disrupt conspecific mating by co‐opting pollinators. Ultimately, this Allee effect may play an important role in determining the long‐term persistence of rarer plants in the landscape, both in terms of seed production and viability. Community context therefore requires consideration when designing and implementing conservation management for plants which are comparatively rare in the landscape. Abstract : Pollinator foraging varies with the diversity, abundance, and spatial configuration of floral resources. We used a landscape‐scale experiment, coupled with microsatellite genotyping, to explore how the floral richness of habitats affected pollinator foraging behavior and pollination services to plants which were experimentally isolated in the landscape. Our findings indicate that locally rare plants are at a competitive disadvantage within florally rich habitats because neighboring plant species disrupt conspecific mating by co‐opting pollinators.